Work-Life Balance and Work Engagement among Employees: The Moderating Role of Perceived Organizational Support - Ulina, Friska; Hardjo, Suryani; Fauzy Indrawan, Yudistira (Psikoborneo: Jurnal Ilmiah Psikologi, 2026)
This study aims to examine the effect of work-life balance on work engagement, with perceived organizational support as a moderating variable. This research is motivated by inconsistent findings in previous studies regarding the relationship between work-life balance and work engagement, as well as the limited exploration of perceived organizational support as a moderating factor. A quantitative explanatory approach was employed using total sampling of 179 employees at PT X in Mandailing Natal Regency. Data were collected using the Work-Life Balance Scale (17 items), Perceived Organizational Support Scale (16 items), and Work Engagement Scale (19 items). Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that work-life balance has a positive and significant effect on work engagement (β = 0.395; p < 0.05), and perceived organizational support also has a positive and significant effect on work engagement (β = 0.255; p < 0.05). Furthermore, perceived organizational support significantly strengthens the relationship between work-life balance and work engagement (β = 0.656; p < 0.05). The model explains 60% of the variance in work engagement. These findings emphasize the critical role of organizational support in enhancing the effectiveness of work-life balance in fostering employee engagement.Penelitian ini bertujuan untuk menganalisis pengaruh work-life balance terhadap work engagement dengan perceived organizational support sebagai variabel moderator. Penelitian ini didasarkan pada adanya inkonsistensi temuan penelitian sebelumnya terkait hubungan antara work-life balance dan work engagement, serta masih terbatasnya kajian yang menempatkan perceived organizational support sebagai variabel moderator. Penelitian menggunakan pendekatan kuantitatif eksplanatif dengan teknik total sampling terhadap 179 karyawan PT X di Kabupaten Mandailing Natal. Pengumpulan data dilakukan menggunakan skala Work-Life Balance (17 item), Perceived Organizational Support (16 item), dan Work Engagement (19 item). Analisis data menggunakan Structural Equation Modeling berbasis Partial Least Squares (PLS-SEM) dengan bantuan SmartPLS 4. Hasil penelitian menunjukkan bahwa work-life balance berpengaruh positif dan signifikan terhadap work engagement (β = 0,395; p < 0,05). Perceived organizational support juga berpengaruh positif dan signifikan terhadap work engagement (β = 0,255; p < 0,05). Selain itu, perceived organizational support terbukti memperkuat pengaruh work-life balance terhadap work engagement (β = 0,656; p < 0,05). Model penelitian mampu menjelaskan 60% variasi work engagement. Temuan ini menegaskan pentingnya peran dukungan organisasi dalam mengoptimalkan pengaruh work-life balance terhadap keterikatan kerja karyawan.